Holding the state at bay: understanding media freedoms in Africa. Issue 7 (9th November 2016) - VonDoepp, Peter; Young, Daniel J.
ABSTRACT: Focused on democratic and hybrid regimes in sub-Saharan Africa, this article explores the factors and conditions that dissuade or restrain governments from clamping down on press freedoms. We suggest that governments might hesitate to interfere with the media for three reasons: they may face excessive political or legal costs for such interference; they might have limited options available to them to curtail media freedoms, and, finally, under some circumstances, governments may obtain a limited payoff from efforts to clamp down on the media. Consistent with anecdotal evidence that motivates some of our hypotheses, our findings suggest that strong media sectors within civil society encourage government respect for media freedoms. We also find that the rule of law is associated with more favourable climates for the media. This likely reflects the protection free media receive from independent judiciaries.